The PDTIS bioinformatics platform: from sequence to function - Otto, Thomas Dan (2007)
Since the eighties, Bioinformatics has acquired a growing importance in the biological sciences. Due to the complexity of hardware and software tools, and the need for a specialized management of network infrastructure, data processing and storage, many research institutions organized a bioinformatics core facility. In this work, we describe typical bioinformatics activities and the organization of a bioinformatics core with institutional support. Since the end of the 80s, FIOCRUZ has contributed for the development and establishment of Bioinformatics in Rio de Janeiro, through different initiatives. Starting with sequence analysis courses, today our institution has a permanent Bioinformatics service, integrated with other strategic activities through a thematic network of technological platforms imbedded in the Program for Technological Development of Health Products (PDTIS), where the main attributions of such platforms are concentrated in support, establishment of new methodologies and active participation in research projects and technological development. In this paper we present the PDTIS Bioinformatics Platform, its scope, resources and its support, teaching and research activities. Bioinformatics has emerged as a new scientific area and a short history of its development at FIOCRUZ is also summarized.